Fluorine-18 (18F)-labeled retinoid x receptor (RXR) partial agonist whose tissue transferability is affected by other RXR ligands. Issue 14 (15th July 2019) - Takamura, Yuta; Shibahara, Osamu; Watanabe, Masaki; Fujihara, Michiko; Yamada, Shoya; Akehi, Masaru; Sasaki, Takanori; Hirano, Hiroyuki; Kakuta, Hiroki
Graphical abstract: Abstract: Bexarotene (1 ), a retinoid X receptor (RXR) agonist approved for the treatment of cutaneous T cell lymphoma (CTCL), was reported to migrate into baboon brain based on findings obtained by positron emission tomography (PET) with a 11 C-labeled tracer. However, co-administration of non-radioactive 1 had no effect on the distribution of [ 11 C]1, probably due to non-specific binding of 1 as a result of its high lipophilicity. Here, we report a fluorine-18 ( 18 F)-labeled PET tracer [ 18 F]6 derived from RXR partial agonist CBt-PMN (2 ), which has lower lipophilicity and weaker RXR-binding ability than [ 11 C]1 . The concomitant administration of 1 or 2 with [ 18 F]6 with resulted in decreased accumulation of [ 18 F]6 in liver, together with increased brain uptake and increased accumulation in kidney and muscle, as visualized by PET. A plausible explanation of these findings is the inhibition of [ 18 F]6 uptake into the liver by concomitantly administered 1 or 2, leading to an increase in blood concentration of [ 18 F]6 followed by increased accumulation in other tissues.